Analysis of the International Research and Development Market: Main Trends in the Development of Participants' Interactions - Liliia MATRAEVA; Ekaterina VASIUTINA; Nataliya KOROLKOVA (Communications of International Proceedings, 2020)
The article analyzes the research and development market operating in various countries of the world. The analysis revealed three basic models for the development of interaction between market participants, features of their modifications, and formed recommendations for the Russian system. Also shows main trends of international market research, based on key indicators, clustering of countries was also carried out, with a description of their specific profiles.
Keywords: International research market; scientific clusters; scientific collaboration; trends in the development of the research and development market.